Spiritual Intelligence with TQN Zikr Method - El Bilad, Cecep Zakarias; Rahman, Abd.; Arifin, Samsul (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2022)
Spirituality is a human spiritual aspect that determines the quality of attitudes and behavior. A lot of cases of immorality are caused by weak spiritual intelligence. Therefore, such intelligence needs to be seriously improved. One of the methods that can be used is reciting zikr (remembrance). This research proves that practicing zikr can have a positive effect on mental condition. This research was conducted at a student boarding school in Palangka Raya who practiced the zikr of the Qadiriyah Naqsyabandiyah Order (TQN). This research is descriptive qualitative as well as quantitative. The result proves that TQN Zikr has a positive impact on the spiritual intelligence of its practitioners. The